Reliability analysis of pile driving formula for concrete driven piles in stiff soil layer: Case study in Chiang Mai Province - Thongmunee S. (2017)
© 2016 Taylor & Francis Group, London. Pile driving formulas, which have been proposed by many researchers, are widely used to predict and control the load carrying capacity of the driven piles. However, efficiency of each formula in predicting the capacity mainly depends on subsoil properties, pile installation data and adopted empirical parameters. In other words, when construction area is different, accuracy of each formula will be changed. The aim of this study is to investigate the appropriate pile driving formula for the area of Chiang Mai province, the largest city in northern Thailand, where the number of construction projects has been increasing rapidly for the last 10 years. In this study, the authors have collected the construction information on concrete driven piles including soil boring log, pile information, installation data and its Dynamic Load Test (DLT). The information was obtained from 7 construction projects around Chiang Mai downtown. Typical soil horizon in all construction sites was found to be alternating layer of stiff silty clay (CL) interbedded with clayey or silty sand (SM or SC). More than 7000 driven piles were installed, and dynamic load tests were performed on 69 selected driven piles in all project. All of the driven pile is square solid concrete pile. Cross section of the driven pile varies from 0.26 × 0.26 m to 0.45 × 0.45 m. Length of the pile varies from 9 to 28 m. Seven pile driving formulas were chosen for predicting the load carrying capacity of the selected DLT piles. The correlation between the predicted capacities and its DLT results were then tested to conduct reliability analysis of the pile driving formulas. The result showed that Gate formula is most reliable formula, based on the higher of R 2 value compared with others for Chiang Mai subsoil.